Psychosocial correlates of deceptive e-cigarette counterfeit susceptibility: a Web's law-persuasion-trait theory perspective. - Muposhi, Asphat; Dhurup, M. (Sabinet Online, 2022)
Deceptive e-cigarette counterfeits are a growing concern for health practitioners and regulators. Web's law, trait theory and persuasion theory were employed to examine psychosocial factors that influence susceptibility to deceptive e-cigarettes. Cross sectional data were collected from 562 South African consumers recruited from five websites that actively promote and sell e-cigarettes. Standard multiple regression analysis results identified sensation seeking, hedonic orientation and perceived authenticity as the main factors influencing susceptibility to deceptive e-cigarette counterfeits. As consumers are influenced by content shared on online e-cigarette platforms, the use of opinion leaders and celebrities to convey messages informing consumers of the dangers of deceptive counterfeit e-cigarettes is imperative. There is also a need to step up the enforcement and monitoring of anti-counterfeit laws to discourage the supply of counterfeit e-cigarettes. Investment in consumer education, research and development is encouraged to come up with innovative e-cigarette attributes that are difficult to imitate.